Weaves and Voices: Tracing the Journey of the Indian Saree. (2nd January 2023) - Chatterjee, Anindita
Abstract: S aree is one of the most popular ethnic Indian garments that enjoy the exclusivity of being reincarnated. It is an integral part of Indian cultural heritage. In the last few years there has been a grand revival of the saree as a popular cultural wear across the nation. Globalization and social media have been highly influential in this resurrection of interest in traditional wear. It all started when two Bengaluru-based friends Anju Maudgal Kadam and Ally Matthan, agreed to wear their sarees 100 times before the end of 2015 and, through social media, encouraged others to do the same. They intended to bring the traditional Indian saree back into their lives, and in the process of reviving the ethnicity they also became storytellers, recounting the histories and narratives woven into each of their sarees. Thereafter the #100sareepact became an Internet sensation, attracting media attention across the world. This paper would like to trace the journey of the Indian saree and also analyze how the saree-pact has forged virtual friendships among women in the Zuckerbergian cyberspace. Apart from creating a new fashion statement across the world it has also resulted in the revival of interest in the traditional Indian weaves.